2015
DOI: 10.1016/j.immuni.2015.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Another TLO in the Wall: Education and Control of T Cells in Atherosclerotic Arteries

Abstract: Atherosclerosis is a lipid-storage disease of arteries that is exacerbated by chronic inflammatory processes. In this issue of Immunity, Hu et al. (2015) demonstrate that T cell responses in atherosclerotic lesions are controlled in tertiary lymphoid organs in the arterial wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Subsequent work placing vascular DCs at the media-adventitia border spatially separated the immunological injury and the tissue-destructive granuloma formation (58)(59)(60). In contrast to atherosclerotic disease, where the adventitia is attracting attention because it is the site of tertiary lymphoid organs (TLOs) (61)(62)(63), GCA-affected arteries do not form organized lymphoid architectures in the adventitia. In an elegant work, Hu et al (62) have implicated localized TLOs in regulating the immune responses promoting atherosclerotic lesions in the murine aorta, affecting T cell recruitment, T cell priming, and induction of regulatory T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent work placing vascular DCs at the media-adventitia border spatially separated the immunological injury and the tissue-destructive granuloma formation (58)(59)(60). In contrast to atherosclerotic disease, where the adventitia is attracting attention because it is the site of tertiary lymphoid organs (TLOs) (61)(62)(63), GCA-affected arteries do not form organized lymphoid architectures in the adventitia. In an elegant work, Hu et al (62) have implicated localized TLOs in regulating the immune responses promoting atherosclerotic lesions in the murine aorta, affecting T cell recruitment, T cell priming, and induction of regulatory T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that TLO support protective immunity against a variety of pathogens (46, 47, 58) or cause tissue damage in inflammatory and autoimmune diseases (15, 6972). Interestingly, presence of TLO in solid tumors correlated with a favorable clinical outcome (18, 19).…”
Section: Discussionmentioning
confidence: 99%